Impaired Early Insulin Response to Glucose Load Predicts Episodic Memory Decline: A 10-Year Population-Based Cohort Follow-Up of 45-74-Year-Old Men and Women - Toppala Sini; Ekblad Laura L.; Viitanen Matti; Rinne Juha O.; Jula Antti (IOS PRESS, 2025)
Background: Diabetes increases the risk for cognitive decline, but the mechanisms behind this association remain unknown. Impaired early insulin secretion in elderly men and insulin resistance, both of which are pathophysiological features of type 2 diabetes, have previously been linked to Alzheimer's disease.
Objective: To examine if the early insulin response to oral glucose load predicts cognitive performance after 10 years in men and women aged 45-74 years.
Methods: This study was based on a subpopulation of the Health 2000 Survey, a Finnish nationwide, population-based health examination study, and its follow-up, the Health 2011 Study. In total, 961 45-74-year-old individuals (mean age at baseline 55.6 years, 55.8% women) were examined. An oral glucose tolerance test was performed in 2001-2002, and early insulin response was defined as the ratio of the 30-min increment in insulin concentration to that of glucose concentration. Cognitive function was evaluated at baseline and follow-up with categorical verbal fluency, word-list learning, and word-list delayed recall. Statistical analyses were performed using multivariable linear models adjusted for age, sex, education, APOE ∈4 genotype, vascular risk factors including diabetes, and depressive symptoms.
Results: A lower early insulin response to glucose load predicted lower performance (β: 0.21, p = 0.03) and greater decline (β: 0.19, p = 0.03) in the word-list delayed recall test. Baseline early insulin response did not predict verbal fluency or word-list learning (all p-values >= 0.13).
Conclusion: Our results suggest that decreased early insulin secretion predicts episodic memory decline in middle-aged to elderly men and women.